Thermophysical properties of the regolith on the lunar far side revealed by the in situ temperature probing of the Chang'E-4 mission. Issue 11 (26th August 2022) - Xiao, Xiao; Yu, Shuoran; Huang, Jun; Zhang, He; Zhang, Youwei; Xiao, Long
Abstract: Temperature probes onboard the Chang'E-4 (CE-4) spacecraft provide the first in situ regolith temperature measurements from the far side of the Moon. We present these temperature measurements with a customized thermal model and reveal the particle size of the lunar regolith at the CE-4 landing site to be ∼15 μm on average over depth, which indicates an immature regolith below the surface. In addition, the conductive component of thermal conductivity is measured as ∼1.53 × 10 –3  W m –1 K –1 on the surface and ∼8.48 × 10 –3  W m –1 K –1 at a depth of 1 m. The average bulk density is ∼471 kg m –3 on the surface and ∼824 kg m –3 in the upper 30 cm of the lunar regolith. These thermophysical properties provide important additional 'ground truth' at the lunar far side, which is critical for the future analysis and interpretation of global temperature observations. Abstract : This paper reports the first in situ temperature and thermophysical properties analysis of the lunar far side regolith at the CE-4 landing site, performed by a customized thermal model, providing ground truth for future global thermophysical studies of the lunar surface.